Answer:
(x + 4)
Explanation:
The given expression is
![x^(2) -5x-36](https://img.qammunity.org/2020/formulas/mathematics/middle-school/eqgjjx7fcoxs1pmn51pzi9kqxh1pmn0rw9.png)
To its factor, we can use the quadratic formula
![x_(1,2)=\frac{-b (+-)\sqrt{b^(2)-4ac } }{2a}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/m4djtmfjmapry5g6nugnn6e1h2gzlt3vyh.png)
Where
![a=1\\b=-5\\c=-36](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3fcv95vm1imw6cudc0vvqkmu2bagwqryol.png)
Replacing these values in the quadratic formula, we have
![x_(1,2)=\frac{-(-5) (+-)\sqrt{(-5)^(2)-4(1)(-36) } }{2(1)}=(5(+-)√(25+144) )/(2) =(5(+-)√(169) )/(2)=(5(+-)13)/(2)\\x_(1)=(5+13)/(2)=(18)/(2)=9\\x_(2)=(5-13)/(2)=(-8)/(2)=-4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2o24ehflte5xlpk9s61uufz6nkvuu1ctah.png)
As you can observe the two factors must be
![(x-9)(x+4)=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/iy1dgoqo4xati7lbm98wchdpfpnomazkhe.png)
Therefore, the right answer is the second choice, (x + 4) is the other factor of the quadratic expression.